Meta-Analysis of Instructional Media to Enhance Writing Skills in Indonesian Language Education - Marlinda, Silviani; Susilowati, Penty; Hilaliyah, Tatu; Hasani, Aceng (Universitas Nusantara PGRI Kediri, 2025)
This study aims to comprehensively identify and analyze the effectiveness of various learning media in improving students’ writing skills within Indonesian language instruction. The research method employed is a quantitative descriptive meta-analysis. Data sources were systematically obtained from 15 academic articles on meta-analysis of learning media and writing skills, accessed primarily through Google Scholar. All selected publications met strict criteria, including a focus on the last five years (2020–2025) and SINTA accreditation status. Data collection utilized purposive sampling, selecting articles based strictly on thematic relevance. Data analysis involved calculating percentages to identify media dominance and conducting qualitative narrative reviews to synthesize findings. The recapitulation of findings reveals that digital media is overwhelmingly the most dominant type of media used (73.33% of the total), compared to analog or traditional media (26.67%). Furthermore, studies focusing on the junior high school level are the most frequent (40%). Crucially, the overall average effect size of the learning media use across all studies is 0.88. This high value falls squarely into the large category, thereby indicating a positive and statistically significant influence on enhancing students' writing skills.